A Reverse-Sandwich Enzyme-Linked Immunosorbent Assay for Verocytotoxin 1 and 2 Antibodies in Human and Bovine Sera - Miyazawa, H. (American Society for Microbiology, 1999)
A reverse-sandwich enzyme-linked immunosorbent assay (ELISA), in which an antibody is sandwiched by antigens, was established for the titration of antibodies to verocytotoxins (VT) in human and animal sera. This assay has two advantages over a conventional indirect ELISA: (i) higher specificity and sensitivity and (ii) the ability to comparably titrate antibodies from different species. The VT1 (Shiga-like toxin 1) antibody-positive rates were 5% in 202 normal adult humans and 99% in 93 normal cattle at a dairy farm. This ELISA is most suitable for seroepidemiologic studies of infections with VT-producing Escherichia coli in humans and various animal species.